Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the equation [tex]\(2x^2 = -10x + 12\)[/tex], we first need to rewrite it in standard form (i.e., setting one side to zero).
### Step-by-Step Solution:
1. Rewrite the equation in standard form:
[tex]\[ 2x^2 + 10x - 12 = 0 \][/tex]
2. Factor the quadratic equation:
To factor [tex]\(2x^2 + 10x - 12\)[/tex], we look for two numbers that multiply to [tex]\(2 \times -12 = -24\)[/tex] and add to [tex]\(10\)[/tex]. After some consideration, we find that these numbers are [tex]\(12\)[/tex] and [tex]\(-2\)[/tex].
So we can rewrite the middle term [tex]\(10x\)[/tex] using these numbers:
[tex]\[ 2x^2 + 12x - 2x - 12 = 0 \][/tex]
3. Group terms to factor by grouping:
[tex]\[ (2x^2 + 12x) + (-2x - 12) = 0 \][/tex]
4. Factor out the common terms in each group:
[tex]\[ 2x(x + 6) - 2(x + 6) = 0 \][/tex]
5. Factor out the common binomial factor:
[tex]\[ (2x - 2)(x + 6) = 0 \][/tex]
6. Solve for [tex]\(x\)[/tex] by setting each factor equal to zero:
[tex]\[ 2x - 2 = 0 \quad \text{or} \quad x + 6 = 0 \][/tex]
7. Solve each equation for [tex]\(x\)[/tex]:
[tex]\[ 2x - 2 = 0 \implies 2x = 2 \implies x = 1 \][/tex]
[tex]\[ x + 6 = 0 \implies x = -6 \][/tex]
So, the solutions to the equation [tex]\(2x^2 = -10x + 12\)[/tex] are [tex]\(x = 1\)[/tex] and [tex]\(x = -6\)[/tex].
### Verifying Against the Given Options:
- [tex]\(x = 3\)[/tex] : Not a solution
- [tex]\(x = -3\)[/tex] : Not a solution
- [tex]\(x = -2\)[/tex] : Not a solution
- [tex]\(x = 1\)[/tex] : Is a solution
- [tex]\(x = -6\)[/tex] : Is a solution
- [tex]\(x = 6\)[/tex] : Not a solution
Thus, the correct answers are [tex]\( x = 1 \)[/tex] and [tex]\( x = -6 \)[/tex].
### Step-by-Step Solution:
1. Rewrite the equation in standard form:
[tex]\[ 2x^2 + 10x - 12 = 0 \][/tex]
2. Factor the quadratic equation:
To factor [tex]\(2x^2 + 10x - 12\)[/tex], we look for two numbers that multiply to [tex]\(2 \times -12 = -24\)[/tex] and add to [tex]\(10\)[/tex]. After some consideration, we find that these numbers are [tex]\(12\)[/tex] and [tex]\(-2\)[/tex].
So we can rewrite the middle term [tex]\(10x\)[/tex] using these numbers:
[tex]\[ 2x^2 + 12x - 2x - 12 = 0 \][/tex]
3. Group terms to factor by grouping:
[tex]\[ (2x^2 + 12x) + (-2x - 12) = 0 \][/tex]
4. Factor out the common terms in each group:
[tex]\[ 2x(x + 6) - 2(x + 6) = 0 \][/tex]
5. Factor out the common binomial factor:
[tex]\[ (2x - 2)(x + 6) = 0 \][/tex]
6. Solve for [tex]\(x\)[/tex] by setting each factor equal to zero:
[tex]\[ 2x - 2 = 0 \quad \text{or} \quad x + 6 = 0 \][/tex]
7. Solve each equation for [tex]\(x\)[/tex]:
[tex]\[ 2x - 2 = 0 \implies 2x = 2 \implies x = 1 \][/tex]
[tex]\[ x + 6 = 0 \implies x = -6 \][/tex]
So, the solutions to the equation [tex]\(2x^2 = -10x + 12\)[/tex] are [tex]\(x = 1\)[/tex] and [tex]\(x = -6\)[/tex].
### Verifying Against the Given Options:
- [tex]\(x = 3\)[/tex] : Not a solution
- [tex]\(x = -3\)[/tex] : Not a solution
- [tex]\(x = -2\)[/tex] : Not a solution
- [tex]\(x = 1\)[/tex] : Is a solution
- [tex]\(x = -6\)[/tex] : Is a solution
- [tex]\(x = 6\)[/tex] : Not a solution
Thus, the correct answers are [tex]\( x = 1 \)[/tex] and [tex]\( x = -6 \)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.